In vitro application of drug-loaded hydrogel combined with 3D-printed porous scaffolds. (1st November 2022) - Huang, Haokun; Wu, Zhenhuan; Yang, Zhuofan; Fan, Xiaoxi; Bai, Siqi; Luo, Junsi; Chen, Minmin; Xie, Xiaoli
Abstract: Titanium mesh and three-dimensional titanium alloy scaffolds play a key role in addressing oral and maxillofacial bone defects, which can provide a specific environment and structure for bone growth and development. The two main causes of implant surgery failure are aseptic loosening and bacterial-induced implant-associated infections. To make bone defect implants effective for a long time, the ideal scaffold should take into account the two functions of osseointegration and anti-infection. Therefore, on the basis of the low-elastic-modulus Ti-10Ta-2Nb-2Zr (TTNZ) alloys developed by the research group in the early stage, this study intends to combine the vancomycin-loaded hydrogel with the 3D-printed through-hole porous titanium alloy scaffold to endow 3D-printed TTNZ scaffolds with antibacterial properties. The antibacterial properties of the complex were investigated by the zone of inhibition test and the adhesion/free antibacterial test. The effects of the composite system on osseointegration were investigated from the aspects of cell adhesion, cell proliferation and osteogenesis-related gene expression. The results showed that loading 2.5 wt.% and 5 wt.% vancomycin did not affect the structure of chitosan–hyaluronic acid hydrogel. The properties of the hydrogels were examined by scanning electron microscopy, Fourier-transform infrared, degradation experiment in vitro and vancomycin release experiment in vitro . When combined with porous scaffolds, the drug-loaded hydrogels exhibited slower drug release rates and longer release times. In addition, in vitro studies found that the TTNZ scaffolds loaded with 5 wt.% vancomycin had a certain effect on the expression of osteogenesis-related genes in cells, but the antibacterial effect was the best. The porous scaffolds loaded with 2.5 wt.% vancomycin hydrogel TTNZ scaffolds did not inhibit cell proliferation, adhesion, alkaline phosphatase activity, and osteogenesis-related gene ex-pression, but the antibacterial effect on free bacteria was not as good as that of TTNZ scaffolds loaded with 5 wt.% vancomycin. This study, complementing the advantages of the two and controlling the local release rate of vancomycin, provides a new idea for future 3D printing of titanium alloy stents for anti-infection.